Brachial-Ankle Pulse Wave Velocity Mediates the Association between Increased Age and Risk of Sarcopenia among Chinese Patients with Type 2 Diabetes Mellitus. (6th January 2023) - Jiang, Jiahong; Zhang, Ping; Zhou, Zijun; Xu, Zeru; Hu, Xiang; Yu, Weihui; Jiang, Feifei; Pan, Yang; Wang, Fei; Hong, Jing; Ye, Tingting; Xu, Ke; et al.
Abstract : Background and Aims . Arterial stiffness and sarcopenia are commonly seen in patients with type 2 diabetes mellitus (T2DM), and both are age-related diseases. However, few studies have addressed the causal relationship between age, arterial stiffness, and sarcopenia, especially in patients with T2DM. This study is aimed at investigating the relationship among age, arterial stiffness, and sarcopenia in patients with T2DM. Methods and Results . This cross-sectional study enrolled 557 inpatients with diabetes at the First Affiliated Hospital of Wenzhou Medical University, China, between June 2020 and July 2021. Patients who were diagnosed with T2DM and underwent examination of dual-energy X-ray absorptiometry, handgrip strength, 6-meter walk speed, and brachial-ankle pulse wave velocity (baPWV, a recognized indicator of arterial stiffness) were enrolled. A total of 447 patients were included. A dose-dependent relationship was found between age and sarcopenia. We also found a dose-dependent relationship between age and baPWV. Similarly, significant dose-dependent relationships were found across baPWV tertiles with higher prevalence of sarcopenia. Then, a mediation analysis was performed to explore the mediation effect of arterial stiffness on age-associated sarcopenia. We found that the prevalence of sarcopenia increased by 0.0115 (95% CI, 0.0028–0.0239) per 1 year increase in age by the mediation effect of baPWV and that the direct effect of aging on sarcopenia was 0.0441 (95% CI, 0.0101–0.0909) per 1 year older. baPWV mediated 20.5% of the positive relationship between increased age and the prevalence of sarcopenia. Conclusions . Elevated baPWV partially mediates the association of age and sarcopenia among patients with T2DM.